Analisa Pengaruh Steam Injection terhadap Overload Continuous Settling Tank (Studi Kasus di PKS XYZ) - St Nugroho Kristono (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
This research discusses the use of steam injection in oil separation process on continuous settling tank (CST) at clarification station, in the palm oil mill (POM) XYZ. Oil that spills on CST, among the causes is the activation of steam injection and is related to the capacity of the CST. The condition will result in oil losses at the clarification station and will affect the decrease of oil extraction rate and the loss for the company. The purpose of this research is to know the optimum steam injection activation time to meet CST level during normal running process. This research was conducted for 1 month and 14 days starting on May 1st to June 14th, 2017 at POM XYZ. Data collection is done by observation and practice directly in the field. Based on the data already obtained, then the analysis of the measurement data will be further processed using a simple mathematical model. The result showed that the optimal steam injection activation time to meet the CST level during normal walking was 2.95 minutes. The injection will fill in the free space on CST, which is 10.0097 m3.